2017
DOI: 10.1093/ejcts/ezw401
|View full text |Cite
|
Sign up to set email alerts
|

Recent improvement of survival prognosis after pulmonary metastasectomy and advanced chemotherapy for patients with colorectal cancer

Abstract: Survival rates of patients after pulmonary metastasectomy for colorectal cancer metastasis who underwent chemotherapy have increased over the years. It implies that newer chemotherapy regimens might have had a positive impact on these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
5
15
0
Order By: Relevance
“…28 Our results demonstrate that even a patient cohort limited to SLLM could show favorable long-term outcomes after resection based on accurate candidate selection; this might also be associated with modern advances in systemic therapies and perioperative management. 29 However, some researchers have indicated that SLLM are unlikely to warrant complete metastasectomy because of their deleterious impact on the prognosis, 19 which might be attributable to patient populations with a heterogeneous tumor biology. Oncologic subclassification in patients with SLLM would be further needed to extend the surgical indications in the era of multidisciplinary approaches to metastatic colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…28 Our results demonstrate that even a patient cohort limited to SLLM could show favorable long-term outcomes after resection based on accurate candidate selection; this might also be associated with modern advances in systemic therapies and perioperative management. 29 However, some researchers have indicated that SLLM are unlikely to warrant complete metastasectomy because of their deleterious impact on the prognosis, 19 which might be attributable to patient populations with a heterogeneous tumor biology. Oncologic subclassification in patients with SLLM would be further needed to extend the surgical indications in the era of multidisciplinary approaches to metastatic colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Only one randomized study comparing PM versus continued active monitoring has been published, although it was discontinued due to poor recruitment rate, thus making the results inconclusive 11 . Moreover, the role of adjuvant chemotherapy for patients treated with PM has been controversial, with studies showing conflicting results 12–14 . Therefore, further research is needed to identify additional prognostic and predictive factors for improved selection of patients with mCRC who will benefit from surgery and adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…China had 245,000 new CRC cases and 139,000 deaths from CRC in 2012, which made it the fifth most common cancer in men and the fourth in women (Gu et al, 2018). Although great advancements have been made in surgical procedures and adjuvant therapies, the overall survival of CRC patients is still poor, especially that of patients at later stages of disease (Fang et al, 2013; Nakajima et al, 2017). However, many CRC patients are initially diagnosed at advanced stages, since early-stage CRC is either asymptomatic or presents with non-specific symptoms (Clarke & Feuerstein, 2018; Hall et al, 2016).…”
Section: Introductionmentioning
confidence: 99%